THE The Relationship between Religiosity and Hardiness in Students Working on Their Thesis at the Faculty of Psychology, Makassar State University - Angreni, Tiara; Razak, Ahmad; Jalal, Novita Maulidya (Polteknik Ilmu Pemasyarakatan, 2025)
Hardiness is a trait that plays an important role in dealing with stressful situations. Coping strategy is one of the factors that affect hardiness, the way to apply coping strategies is by having faith or joining a religious community called religiosity. The purpose of this study was to determine whether there is a relationship between religiosity and hardiness in students who are working on a thesis at the Faculty of Psychology, Makassar State University. This study used a quantitative correlation approach involving 168 students as respondents. The scale used in this study is the Hardiness and Religiosity scale. Spearman Rho correlation analysis showed a significant relationship between Hardiness and Religiosity in the intellectual dimension (r=0.048, p<0.05), ideology (r=0.011, p<0.05), and public worship (r=0.016, p<0.05), which indicates a significant relationship between Hardiness and religiosity. This finding has implications that increasing religiosity can strengthen students' hardiness, so it is important for students and educational institutions to develop spiritual aspects and mental resilience during the thesis process.